ANALISIS PROMOSI PERPUSTAKAAN MELALUI MEDIA SOSIAL INSTAGRAM DI UPT. PERPUSTAKAAN - ekasari, Ni Luh Dewi; Haryanti, Ni Putu Premierita; Ginting, Richard Togaranta (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
This research analyzes how promotional strategies are implemented by UPT. Gadjah Mada University Library via social media Instagram. The research method used is descriptive qualitative with purposive sampling technique. The aim is to understand the use of the Instagram platform as a medium for promoting library services to users. Data was obtained through interviews with the head of library services, library staff, library users and analysis of content uploaded to Instagram accounts. Results indicate promotional strategies, including educational content, collection information, and promotion of events and services. This research illustrates the significance of Instagram as an effective tool in expanding the reach of library promotions. This research is expected to provide insight for UPT. Gadjah Mada University Library and similar institutions in optimizing the use of social media for service promotion.   Keywords: Technology, Instagram, Users, Promotion, Library.